2001
DOI: 10.1038/sj.cr.7290078
|View full text |Cite
|
Sign up to set email alerts
|

Maternal zinc deficiency impairs brain nestin expression in prenatal and postnatal mice

Abstract: Effects of maternal dietary zinc deficiency on prenatal and postnatal brain development were investigated in ICR strain mice. From d 1 of pregnancy (E0) until postnatal d 20 (P20), maternal mice were fed experimental diets that contained 1 mg Zn/kg/day (severe zinc deficient, SZD), 5 mg Zn/kg/day (marginal zinc deficient, MZD), 30 mg Zn/kg/day (zinc adequately supplied, ZA) or 100 mg Zn/kg/day (zinc supplemented, ZS and pair-fed, PF). Brains of offspring from these dietary groups were examined at various devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 24 publications
1
26
2
Order By: Relevance
“…The abnormalities were not reversed by dietary zinc supplementation after weaning [3]. Further study showed that the nestin protein levels in the developing brain of zinc-deficient groups were lower than those of zinc-supplemented groups, and the level correlated with the amount of dietary zinc consumed by the mother [4]. These findings suggested that zinc deficiency suppresses development of neural stem cells, an effect which might lead to neuroanatomical and behavioral abnormalities in adults.…”
Section: Introductionmentioning
confidence: 96%
“…The abnormalities were not reversed by dietary zinc supplementation after weaning [3]. Further study showed that the nestin protein levels in the developing brain of zinc-deficient groups were lower than those of zinc-supplemented groups, and the level correlated with the amount of dietary zinc consumed by the mother [4]. These findings suggested that zinc deficiency suppresses development of neural stem cells, an effect which might lead to neuroanatomical and behavioral abnormalities in adults.…”
Section: Introductionmentioning
confidence: 96%
“…In support of this, ethanol exposure during organogenesis has been demonstrated to inhibit neuronal differentiation and proliferation (29) and cause apoptosis in cell populations, such as the developing neural plate and primitive streak (30). Suppression of normal neural stem cell development has been similarly demonstrated by a deficiency of dietary Zn throughout pregnancy (31,32). This could interfere with subsequent developmental stages (migration or differentiation), leading to major structural changes in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the newborn neurons migrate to the granular layer and extend mossy fiber axons, indicating that they are integrated into the functional circuitry of the hippocampus (Gould et al 1999;Markakis andGage 1999, van Praag et al 2002;Joo et al 2007). Recently, it has been reported that maternal zinc deficiency impaired microtubule-associated protein-2 expression and reduced numbers of nestin-positive stem cells in prenatal and postnatal mouse brain (Wang et al 2001;Wang et al 1999). It has also been reported that zinc deficiency impairs neurogenesis by regulating p53-dependent molecular mechanisms (Corniola et al 2008).…”
Section: Introductionmentioning
confidence: 91%